Revision of the family Carabodidae (Acari, Oribatida) V. Fourth part. Two new species of the genus Congocepheus from the Republic of Rwanda: Congocepheus rwandensis sp. n., and Congocepheus kayoveae sp. n. - Fernandez, Nestor (2016)
Two new species from Rwanda are described utilizing optical and scanning electron microscope observations: Congocepheus rwandensis sp. n. and Congocepheus kayoveae sp. n. are compared to Congocepheus taurus Balogh 1961.